The effect of hoof trimming on dairy cows´ behaviour, locomotion and production - Back, Jeanette (2010)
The Swedish dairy production today consists of big farms and different housing systems are in use. These systems put demands on the cows’ ability to cope with the environment and one challenge is the claw health in the herds. Some claw lesions that are frequently observed are foot rot, hemorrhages, digital dermatitis and sole ulcers, which can be caused by, for example, the claws’ environment and the flooring type used. The flooring type decides how great the wear is and how the wear pattern will be. Too great wear results in a thinner more sensitive sole while a too small wear causes overgrowth, which increases the pressure on local spots. Both of these wear patterns results in an increased risk of claw lesions and to decrease this risk, routine claw trimming is performed. The number of trimmings a year varies from trimming when needed up to three times a year (recommendations state twice a year). The purpose of the trimming is to redirect the pressure to the claw’s wall, which is the strongest part. This is achieved by trimming the claw to a correct angle and by dishing out some of the medial sole. Claw trimming have many proved positive effects, but a possible problem with lameness caused by the trimming process has also been noticed. This was considered in need of an investigation and this study has focused on the trimming process, what factors that could be causing the lameness and if there really is a problem. This was achieved by studying cows locomotion on three farms before and after trimming, the trimming was also observed to notice factors that could affect the locomotion. The possible factors involved in affecting the cows’ locomotion after trimming are many and are at a high proportion connected to the handling of the cows during the trimming. Some of these factors were found to be slippery floors which caused strains as well as crush or break injuries caused by the restraining of the claws in the trimming chutes. The lameness was found to be, in many cases, a product from treated claw lesions, however not all cows that were treated for claw lesions became lame and cows that were not affected with claw lesions also suffered from a decreased locomotion after the trimming. The locomotion was found to be significantly affected by the trimming and it remains to investigate which factors are causing this One factor of particular interest for further research is break injuries due to the restraining of the front claws to the trimming chutes, which was observed as a swelling at the joint after the trimming. A significant connection between poor locomotion and decreased milk yield could not be found but there was a tendency towards this and a greater data set is needed to establish this.